水素エネルギー循環社会構築への一考察 - 生嶋 素久; Motohisa Ikushima; 宮城大学事業構想学部; Miyagi University School of Project Design
The environmental tolerance should not exceed the global self-purification capacity. The industrial revolution that began with the invention of the steam engine is the large scale of energy consumption industry, and creates out electricity and car civilized society. When it tries to arrange the energy resource with firewood, coal, petroleum, natural gas, methane hydrate, the hydrogen of the energy efficiency is better than that of the carbon in the direction of the decarbonization element, decarbonization element will show the new industry society.